Construcción de los personajes discapacitados femeninos en la novela Las primas de Aurora Venturini - Ontaneda Roblez, Karla Dayanna (2024)
This research aimed to analyze the construction of disabled female characters in Aurora Venturini's Las primas. The methodological approach applied was a documentary design. The corpus considered for this research was the complete novel Las primas by Aurora Venturini, and a table with categories and topics was employed to extract and organize data in relation to the study objectives. The results showed various social factors from an intersectional analysis related to disability, such as gender, sexuality, age, and socioeconomic status. These factors contributed to the construction of disabled female characters and showed that they are not exempt from female stereotypes. The construction of their bodies is based on a mark associated with their progenitors' sin, also offering a perspective of abuse in terms of reproduction and sexuality. Additionally, through the use of narrative discourse analysis, dehumanization and violence towards disabled female characters were found, such as animalization, references to the monstrous and abnormal, and feelings of repulsion. The novel has provided a critical view of the factors that contribute to the construction of these disabled women, both in their bodies and in their images through narrative discourse.